Anther Culture of BC1F1 (KDML105//IRBB5/KDML105) Hybrid to Produce Bacterial Blight Resistance Doubled Haploid Rice - Supanyika Sengsai; Surin Peyachoknagul; Prapa Sripichitt; Amara Thongpan; Pradit Pongtongkam (Agriculture and Natural Resources, 2007)
Maltose was found to be a better carbon source for callus induction in BC1F1 (KDML 105//IRBB5/KDML105) anther culture compared with sucrose. Statistical analysis, however, showed that increasing maltose or sucrose concentrations had no differential promotive effects on callus formation. One-step plantlet formation was found when maltose and NAA were supplemented together in the induction media. Adding 2 mg/l 2,4-D to the medium further increased the percentage of callusing anthers from 5.57% to 10.19%. However, the highest percentage of green plant regeneration was obtained (1.29%) from calli induced on N6 medium without 2,4-D and subsequently cultured on regeneration medium containing MS supplemented with 2 mg/l BAP, 0.2 mg/l NAA, 300 mg/l casein hydrolysate, 15% coconut water, and 30 g/l sucrose. AFLP analysis of all six anther-derived plants showed 57.3% to 67.12% recurrent parental alleles. After planting, seeds were detected in two out of six anther culture-derived plants indicating the occurrence of spontaneous chromosome doubling in these plants. Unfortunately, none of these six plants contained bacterial blight resistant gene (xa5) as detected by specific PCR-based RG556 marker and pathogen inoculation.